The effects produced by molecular ions on a solid surface - Kononenko, S.I.; Muratov, V.I. (Вопросы атомной науки и техники, 2003)
This work deals with the experimental study of secondary electron emission induced by discusses 1 MeV/a.m.u. hydrogen ions in forward direction from thin argentums, copper and nickel foils. The possible reasons of less effective generation of law energy electrons by molecular ions were discussed. We concluded that realization of collision mechanism of secondary electron production (slow electrons) is complicated by correlative motion of the constituent ions of molecule in the substance. The experiments show, that when fast charged particle passes through substance the production mechanism of ionization electrons through plasma oscillations, apparently, is proved to be more effective for molecular ions, than for atomic ones. У цій роботі приведені результати експериментального дослідження вторинної електронної емісії, що спричинюється іонами водню з енергіями 1 MeВ/a.о.м.. Емісія вивчалася на простріл з тонких мішеней зі срібла, міді і нікеля. Обговорюються можливі причини менш ефективної генерації низько енергетичних електронів молекулярними іонами. Ми вважаємо, що механізм створення повільних електронів через зіткнення має певні труднощі, щодо реалізації при корелірованому розльоті фрагментів молекулярного іона в речовині. Проведені експерименти показали, що передача енергії від швидкої зарядженої частинки електронам середовища через плазмові коливання найбільш ефективно для молекулярних іонів, ніж для атомних. В этой работ приведено результаты экспериментального исследования вторичной электронной эмиссии, вызываемой ионами водорода с энергиями 1 MэВ/a.е.м.. Эмиссия изучалась на прострел с тонких мишеней из серебра, меди и никеля. Обсуждаются возможные причины менее эффективной генерации низкоэнергетических электронов молекулярными ионами. Мы считаем, что столкновительный механизм создания медленных вторичных электронов затруднен при коррелированном разлете фрагментов молекулярного иона в веществе. Проведенные эксперименты показали, что передача энергии от быстрой заряженной частицы электронам среды посредством плазменных колебаний более эффективно для молекулярных ионов, чем для атомных.